Serous papillary adenocarcinoma possibly related to the presence of primitive oocyte-like cells in the adult ovarian surface epithelium: a case report - Virant-Klun, Irma; Skutella, Thomas; Cvjeticanin, Branko; Stimpfel, Martin; Sinkovec, Jasna (Journal of ovarian research, 2011)
The presence of oocytes in the ovarian surface epithelium has already been confirmed in the fetal ovaries. We report the presence of SSEA-4, SOX-2, VASA and ZP2-positive primitive oocyte-like cells in the adult ovarian surface epithelium of a patient with serous papillary adenocarcinoma.